Research trends in transient receptor potential vanilloid in cardiovascular disease: Bibliometric analysis and visualization - Zhang, Lingfeng; Xu, Yantao; Ma, Yingxu; Xie, Tianjian; Liu, Chan; Liu, Qiming (Frontiers in Cardiovascular Medicine, 2023)
Abstract Objective: This study aims to accomplish a comprehensive bibliometric analysis. Trends and public interest since TRPV have been reported for the first time. Methods: The article summarized the Web of Science Core Collection. Bibliometric metrics were analyzed and visualized with R package bibliometrix, CiteSpace, and VOSviewer. The map was painted in GunnMap 2 (lert.co.nz). Results: After duplicated data, books, conference proceedings, and uncertain aged articles were removed, 493 were included, and 17 publications were excluded. The distribution of publications by year showed that the number of publications rose sharply from 2008 onwards and either reached a peak in 2021 or has yet to reach a peak. The geographical distribution indicated a large gap between the number of publications in the United States, China, and other countries and East Asian institutions leading the world’s trends in this field. The co-authorship analysis showed that 77 top institutions were grouped into 19 clusters, each covering approximately a single country, suggesting that international cooperation among institutions should be strengthened. The core author extraction revealed changes in the most prolific authors. The keyword analysis revealed clustering and top citation bursts. The co-citation analysis of references from 2011 to 2021 showed the number of citations and the centrality of the leading articles. Conclusions: This study revealed trends and public interest in transient receptor potential vanilloid for cardiovascular disease. Our findings suggest that the field has been proliferating after 2008, has several core authors, and that the United States and China are taking the lead position. In addition, inter-country cooperation should be strengthened, and future research hotspots may focus on pharmacological mechanisms and in-depth exploration of drug clinical trials, efficacy prediction, prediction of adverse effects, and new clinical disease application areas, such as hypertension, diabetes, and cardiac arrhythmias, which may pave the way for further research. Keywords: transient receptor potential vanilloid; TRPV; cardiovascular disease; CVD; bibliometric analysis